Development and optimization of an injectable in-situ gel system for sustained release of anti-tuberculosis drugs - Pooraniammal Balu; Srimari Srikanth; Divya Prakash Gnandhas; Ramya Devi Durai; Venkasubramanian Ulaganathan; Vedha Hari B Narayanan (Scientific Reports)
Abstract Addressing the challenges of drug-resistant Mycobacterium tuberculosis requires regular drug intake and consistent therapeutic drug concentrations, for which in-situ gel systems offer a promising solution by enabling sustained drug release. This study aims to develop an injectable system for chronic tuberculosis treatment, focusing on an in-situ gel formulation created using Poloxamer 407, Carbopol 940, and Hydroxy Propyl Methyl Cellulose (HPMC). The experiments involved a combination of two FDA-approved first-line anti-TB molecules, namely Rifampicin (RIF) and Isoniazid (INZ), by loading in the in-situ gel (IGS) formulations prepared by cold process. The gelling polymers were varied at three levels of concentration and optimized through the molecular docking method, wherein the blend of polymers with drugs showed the docking score of − 3.085. The physicochemical properties and analytical characterization, including gelation temperature, drug content, FT-IR, SEM, TG-DSC, in-vitro drug release, ex-vivo permeation, and cytotoxicity, were performed. According to the study results, the optimized gelation temperature was 26 °C, the viscosity of the sol and gel was 238 cP and 1700 cP, respectively, with the maximum drug content (RIF 100 ± 2.17% and INZ 97 ± 1.31%). The FTIR analysis confirmed the stability of drugs, the morphological study using SEM showed the formation of a network structure, and thermal analysis by TG-DSC confirmed the solid-state transition of drugs. The in-vitro drug release studies in phosphate buffer pH 7.4 showed sustained release of Rifampicin and Isoniazid for up to 10 days and 6 days, respectively. The selected formulation exhibited non-toxic effects in the L929 cell line. Based on the results, in-situ gel administration could be recommended for intramuscular administration for sustained release of the drugs, which is expected to reduce the dosing frequency and improve patient compliance for chronic tuberculosis therapy.